Answer:
b = - 2, b = 4
Explanation:
Using the distance formula
d =
![\sqrt{(x_(2)-x_(1))^2+(y_(2)-y_(1))^2 }](https://img.qammunity.org/2022/formulas/mathematics/high-school/bvn9gyn3kb5znjatyo0ybqks09f51n4oea.png)
with (x₁, y₁ ) = M(3, 1) and (x₂, y₂ ) = N(- 1, b)
d =
![√((-1-3)^2+(b-1)^2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/3p50cem53qoutr2zim8l15op1scyorx2y1.png)
=
![√((-4)^2+(b-1)^2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/nngdkc0ozsdypu8eplmrtwl3mns590iuws.png)
=
![√(16+(b-1)^2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/8roiz0kfxnmgb05oic9lhlomm2eryvypr5.png)
Then
= 5 ( square both sides )
16 + (b - 1)² = 25 ( subtract 16 from both sides )
(b - 1)² = 9 ( take square root of both sides )
b - 1 = ±
= ± 3 ( add 1 to both sides )
b = 1 ± 3
Then
b = 1 - 3 = - 2 or b = 1 + 3 = 4